THE EVALUATION ON THE THOUGHTS OF THE STUDENTS ABOUT “THE BASIC ISLAMIC INFORMATION” COURSE IN THE DEPARTMENT OF PRIMARY RELIGIOUS CULTURE AND MORAL EDUCATION IN THE FACULTY OF ISLAMIC SCIENCES. (BARTIN UNIVERSITY CASE) - Hasan KURT (Fırat University, 2019)
In this article, thoughts of the students were reviewed, who took the course titled “Basic Religious Sciences I” at the Bartın University, Faculty of Islamic Sciences, Department of Primary Education Religious Culture and Moral Knowledge. In this course, issues regarding to the Islamic creed and subjects of the Islamic Theology are taught. In the introduction of the article, historical survey of Theology and Faculty of Islamic Sciences and Department of Primary Education Religious Culture and Moral Knowledge is given. Moreover, basic information about the “Basic Religious Sciences I” course is given. The information about these departments is provided from the Official Gazette and official websites of the faculties. In the part of Methodology, technical information is given on the study’s research design, method, sample, data collection and data analysis. In the results, data of the questionnaire, which was applied to the students and aimed to show their views on the fundamentals of faith, is examined. In the conclusion, the evaluations are made on both the historical process and the findings. This study is done in order to articulate better course schedule for the students who take “Basic Religious Sciences I” course in the newly founded universities in general in the case study of Bartın University Faculties of Islamic Sciences. It is thought that this study will contribute to forthcoming studies with respect to its originality as interdisciplinary study and its deal with current issues in Islamic theology and its becoming one of the first studies on the newly founded departments in Turkey.